PENGARUH PERBEDAAN SENAM RHYTHMIC AUDITORY STIMULATION (RAS) DAN HIGH INTENSITY INTERVAL TRAINING (HIIT) TERHADAP PENINGKATAN ENDURANCE PADA SISWA SEKOLAH DASAR (SD) - Fauziyah Rofifatul Huda; Siti Khotimah (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Elementary school children aged 10-12 years experience a decrease in endurance such as lack of sports activity. At this age physiological changes occur (the body's metabolic system begins to adjust to greater energy needs). Decreased endurance can affect health, cognitive and concentration while learning. To increase endurance, the intervention given is Rhythmic Auditory Stimulation (RAS) and High Intensity Interval Training (HIIT). Objective: To determine the effect and difference of rhythmic auditory stimulation (RAS) and high intensity interval training (HIIT) on increasing endurance in elementary school students. Methods: This study used quasi experimental method with pre and post two group design. A total of 30 samples were determined using purposive sampling technique. The sample was divided into 2 groups of 15 respondents each with the intervention of Rhythmic Auditory Stimulation (RAS) and High Intensity Interval Training (HIIT). Exercise is carried out for 4 weeks with a frequency of training 3 times a week. The measuring instrument used was the Harvard Step Test. Normality test using Saphiro-wilk test. Homogeneity test using lavene test, hypothesis test I and II using paired sample t-test, and hypothesis test III using Independent sample t-test. Results: The results of hypothesis tests I and II using paired sample t-test obtained p = 0.000 (p <0.05). While the third hypothesis test using independent sample t-test obtained a value of p = 0.000 (p <0.05). Conclusion: There is an effect and difference in rhythmic auditory stimulation (RAS) and high intensity interval training (HIIT) on increasing endurance in elementary school students. Keywords: Endurance; Senam Rhytmic Auditory Stimulation (RAS), High Intensity Interval Training (HIIT); Harvard Step Test; Elementary School Students